Cytotoxicity of separation orthodontic elastics - Santos,Rogério Lacerda dos (2012)
OBJECTIVE: To test the hypothesis that there is no difference in cytotoxicity between separating elastics of different manufacturers. METHODS: The present article compared latex elastics (4.0 mm, 4.4 mm and 4.8 mm) of four different manufacturers. The sample was allocated to seven groups of 9 elastics: Group A (American Orthodontics, green color, modules), Groups M1 and M2 (Morelli, blue color, modules and free in pack respectively), Groups M3 and M4 (Morelli, green color, modules and free in pack respectively), Group U (Uniden, blue color, free in pack) and Group T (Tecnident, blue color, free in pack) regarding their possible cytotoxic effects on oral tissues. Cytotoxicity assays were performed using cell culture medium containing epithelioid-type cells (Hep-2 line) derived from human laryngeal carcinoma and submitted to the methods for evaluating the cytotoxicity by the "dye-uptake" test, at time intervals 24, 48, 72 and 168 h. Data were compared by analysis of variance (ANOVA) and Tukey's test (p < 0.05). RESULTS: Results showed statistically significant difference (p < 0.05) between group U and all the other Groups (A, M1, M2, M3, M 4 and T) at 24 and 48 hours. CONCLUSIONS: Uniden elastics evoked more cell lysis at 24 and 48 h, although, all brands showed biocompatibility from 72 h onwards.